2022
DOI: 10.1145/3524111
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Taboos and Euphemisms in Nepali

Abstract: Languages across the world have words, phrases, and behaviors - the taboos - that are avoided in public communication considering them as obscene or disturbing to the social, religious, and ethical values of society. However, people deliberately use these linguistic taboos and other language constructs to make hurtful, derogatory, and obscene comments. It is nearly impossible to construct a universal set of offensive or taboo terms because offensiveness is determined entirely by different factors such as socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Over time, I noticed changes in students' use of informal everyday language style, particularly the use of Thai impolite title ai (Leetrakul, 1978) before name-calling in my presence, which would be considered inappropriate in most contexts in Thai society. Using slang, taboo, and/or impolite language signals in-group identity (Niraula et al, 2022), which means students considered me as one of the peers whom they included in their discussions. As a result, this data confirmed that I successfully negotiated my teacher identity to be one of them.…”
Section: Teacher As An Old-timer and A Peermentioning
confidence: 99%
“…Over time, I noticed changes in students' use of informal everyday language style, particularly the use of Thai impolite title ai (Leetrakul, 1978) before name-calling in my presence, which would be considered inappropriate in most contexts in Thai society. Using slang, taboo, and/or impolite language signals in-group identity (Niraula et al, 2022), which means students considered me as one of the peers whom they included in their discussions. As a result, this data confirmed that I successfully negotiated my teacher identity to be one of them.…”
Section: Teacher As An Old-timer and A Peermentioning
confidence: 99%
“…It is the official language of Nepal and several eastern Indian regions, including Sikkim, Darjeeling, and Kalimpong. It is spoken by more than 20 million people, mainly in Nepal and other places worldwide, including Bhutan, India, and Myanmar (Niraula, Dulal, and Koirala 2022).…”
Section: Introductionmentioning
confidence: 99%